Trends in Using Passive Thermal Imaging Diagnostics in Power Engineering and Industry - Vavilov V. P. Vladimir Platonovich; Demin V. G.; Shiryaev V. V. Vladimir Vasilyevich; Nesteruk D. A. Denis Alekseevich (2003, 2003)
Title screen